Digital Culture as a Factor of Efficiency and Reducing the Risks of Digital Transformation of the Economy and Society - B. N. Panshin (Цифровая трансформация)
Approaches to assessing the role of digital culture in reducing risks and increasing the efficiency of digital transformation of the economy and society in the context of its constant acceleration are considered. The list and characteristics of the risks of digital transformation at the mega-, macro-, micro-levels and the level of the individual are given. The issues of the development of the concepts of digital culture and digital transformation are discussed and interpretations of these concepts are given, taking into account the importance of socio-cultural factors in the context of achieving synergistic effects of digital transformation. The necessity of the formation of digital transformation engineering and the engineering of digital culture as new areas of research in the field of digitalization is substantiated.